Exploring the iceberg of gluten - Chaudhary, Bhupendra; Chaudhary, Ansh (International Journal of Contemporary Pediatrics, 2020)
Gluten, a protein present in wheat, rice or barley shares the reputation of common etiological agent for childhood disease ‘Coeliac Disease’ (CD) and adult ‘Non-Coeliac Gluten Sensitivity’ (NCGS).